TRANSFORMATION IDENTITY THROUGH DIGITAL COMMUNICATION IN MOHSIN HAMID’S EXIT WEST - Sukanya, Priya; M. P. Ganesan (International Journal of Research -GRANTHAALAYAH, 2026)
In Mohsin Hamid’s Exit West, technology plays an vital role in shaping identity and relationships. The story follows Saeed and Nadia, young lovers living in a city affected by war. To stay in touch and for survival, they depend on both digital communication tool and magical technologies like cell phones and The Magical Doors. These Magical Doors are a metaphorical symbol of technology, which acts as a portal and helps Saeed and Nadia to break physical barriers and enables travel to different parts of the world. While technology makes them connect with each other, it also brings the feeling of isolation and disconnection from reality. The present paper explores the impact of technology on identity, relationships and sense of belonging to the new environment. The dual nature of technology brings new opportunities and challenges. This paper aims to show that while technology helps Saeed and Nadia stay in touch and escape, it also makes them feel isolated and disconnected from reality. Saeed and Nadia's journey shows technology impacts human experiences, especially in a migration and globalized world. The research paper provides a deeper understanding of how technology shapes identity and belonging in a rapidly evolving world.